The Use of Apremilast in Psoriasis: An Indian Perspective on Real-World Scenarios - Rajagopalan M; Dogra S; Saraswat A; Varma S; Banodkar P (Dove Medical Press, 2021)
Murlidhar Rajagopalan,1 Sunil Dogra,2 Abir Saraswat,3 Sachin Varma,4 Pravin Banodkar5 1Department of Dermatology, Apollo Hospitals, Chennai, Tamilnadu, India; 2Department of Dermatology, Venereology & Leprology, PGIMER, Chandigarh, India; 3Indushree Skin Clinic, Lucknow, Uttar Pradesh, India; 4Skinvita Clinic Kolkata, Department of Dermatology, Apollo Hospital, Kolkata, West Bengal, India; 5Skin Crest Clinic, Mumbai, Department of Dermatology, Saifee Hospital, Breach Candy Hospital, and St. Elizabeth's Hospital, Mumbai, Maharashtra, IndiaCorrespondence: Murlidhar RajagopalanDermatology, Apollo Hospital, No 21, Greams Lane, Off Greams Road, Chennai, 600006, Tamil Nadu, IndiaTel +91 9840045500Email docdhoot@gmail.comAbstract: Apremilast, an oral phosphodiesterase-4 inhibitor, is approved for use in the management of psoriasis and psoriatic arthritis. Although its efficacy and safety have been well established in clinical studies, in real-world settings, different practice scenarios have been reported. This review paper serves to evaluate clinical real-world scenarios and aspects of treatment for which the information in the literature was considered to be lacking or controversial. Following a literature review, a panel of five dermatologists with expertise in psoriasis considered five scenarios; namely, the positioning of apremilast in psoriasis, its use in difficult-to-treat areas, special conditions and populations, safety, dose titration and dose in maintenance therapy. These were then assessed with psoriasis experts in India using a web-based questionnaire. A total of 28 questions were discussed regarding these scenarios. According to the responses, apremilast is effective in stable mild to moderate psoriasis as monotherapy and in severe psoriasis in combination. Also, a positive response was received with regard to its effectiveness in difficult locations such as the scalp, palms and soles. To reduce adverse effects, prolonged titration therapy over 4 weeks is required and lower doses can be prescribed to maintain remission. Apremilast therapy should be continued for a minimum of 8 weeks once initiated to achieve the desired results, and the total duration of therapy should be about 24 weeks for better efficacy. It is also effective in many other cases, such as obese patients, patients with hepatitis B or C and HIV, or patients on polypharmacy. It was also reported that apremilast requires less prescreening and monitoring than other conventional and biologic systemic therapies. Overall, apremilast is an attractive option for the individualized treatment of psoriasis owing to its favorable safety profile, its ease of oral administration without the need for screening or ongoing laboratory monitoring, and its positive impact on symptoms and lesions in difficult-to-treat areas.Keywords: apremilast, psoriasis, titration, real world, safety